Madagascar : Land and Property Rights Review - World Bank (World Bank, Washington, DC, 2021)
This Review attempts to be a timely input into the legal and policy reform agenda and the implementation process on which the Government has embarked. The report has been elaborated in close partnership with the National Land Tenure Reform Program (Programme National Foncier). It has been benefited from the input of a number of independent consultants, whose names and papers are listed in Annex 3. The report investigates some of the major land-related issues under the following headings: (i) overview of land tenure and land markets; (ii) the current property rights regimes (statutory and customary); (iii) the economic benefits of the current land titling system; (iv) open access and natural resources; (v) private sector issues; (vi) reforms underway and outstanding; and (vii) the piloting and implementation strategy. The main recommendations of the report are summarized in matrix form in Annex 1.